1996
DOI: 10.1159/000262163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Hypochlorite Treatment on Remineralization of Human Root Dentine in vitro

Abstract: Dentine consists simplified of mineral and of several organic components. Sodium hypochlorite (NaOCl) is a well-known nonspecific proteolytic agent capable to remove organic material. The aim of this study was to investigate the influence of organic material removal from artificial dentine lesions by means of NaOCl pretreatment on subsequent remineralization with and without fluoride. Human root dentine samples were demineralized in an acidic gel (pH = 5) at 37°C for 2 weeks. After 2 min of pretreatment with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 9 publications
3
40
0
6
Order By: Relevance
“…The highest mean calcium content that was recorded in group V a (Saline) compared to group V b (did not receive any irrigation) could be explained by the variable effect of NaOCl as irrigating solution on mineral content of root dentin, where it has been reported that treatment with sodium hypochlorite may causes mineral accumulation in human root dentin (33) . Moreover, it has been demonstrated that the use of 2.5% sodium hypochlorite as irrigation solution, either alone or combined with a 17% EDTA solution, significantly increases the Ca/P ratio of root dentin (18) .…”
Section: Discussionmentioning
confidence: 91%
“…The highest mean calcium content that was recorded in group V a (Saline) compared to group V b (did not receive any irrigation) could be explained by the variable effect of NaOCl as irrigating solution on mineral content of root dentin, where it has been reported that treatment with sodium hypochlorite may causes mineral accumulation in human root dentin (33) . Moreover, it has been demonstrated that the use of 2.5% sodium hypochlorite as irrigation solution, either alone or combined with a 17% EDTA solution, significantly increases the Ca/P ratio of root dentin (18) .…”
Section: Discussionmentioning
confidence: 91%
“…From the observation that the surface layer did not hypermineralize we conclude that the tubules remained open and are available for ion transport. Other investigators [Inaba et al, 1996] have shown rapid hypermineralization after hypochlorite treatment, which removed the organic content or lining of the tubules, thus improving crystal growth conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, Kogan et al (6) investigated the effects of various additives on setting properties of MTA and showed that MTA mixed with NaOCl gel improved the setting process. NaOCl is also known as a halogenated compound that can cause mineral accumulation in human root dentin (19). With respect to this, Uyanik et al (20) reported that the sealing ability of furcal perforation repaired with MTA was affected by exposure to the irrigation regimens and the samples irrigated with NaOCl had the lowest leakage values.…”
Section: Discussionmentioning
confidence: 99%